PENYUSUNAN LAPORAN KEUANGAN BERBASIS APLIKASI ACCURATE ONLINE SEBAGAI DASAR PENGUKURAN KINERJA KEUANGAN (STUDI KASUS PADA CV BAGUS AGRISETA MANDIRI) - Falakh, Logi Ahmad; Indrawan, Andi Kusuma; Wijayanti, Rika (Cahaya Ilmu Bangsa, 2025)
This research aims to prepare financial statements based on the Accurate Online application and measure financial performance based on financial ratio standards set by the Regulation of the Minister of State for Cooperatives and Small and Medium Enterprises Number 06/Per/M.KUKM/V/2006 at CV Bagus Agriseta Mandiri. This research uses applied methods, namely the preparation of Accurate Online-based financial statements at CV Bagus Agriseta Mandiri and measuring financial performance. The results of the study prove that financial performance based on MSME financial ratio standards shows very good criteria from various components, but the preparation of financial reports is still manual using Microsoft Excel. Companies need to compile financial reports and record transactions using Accurate Online, in order to increase efficiency when recording transactions and financial reporting that are processed automatically.